Hubungan Antara S Tatus Demensia dengan Disabilitas Fungsional pada Lansia di Desa Gonilan Kartasura - , Maftukhah; , Ambarwati, S.Pd, M.Si; , Sri Darnoto S.KM M.PH (2013)
The aging process is a process which is followed by some physical decline. It is usually followed by the emergence of a variety of psychological, cognitive, affective, and psychosocial disorders. One of the cognitive interferences experienced by the elderly is the dimensia. Dimensia is the effects that occur from psychological changes in the form of cognitive decline. The aims of this research are to know the relationship between the status of the dimensia with functional disabilitas of the elderly in Gonilan Kartasura. The type of the research is observational analytic research using Cross Sectional approach. This research was conducted in Gonilan Kartasura with the number of the elderly sample of research are 75 who meets the criteria of inclusion. Dimensia was measured with the use of Mini Mental State Examination (MMSE), and functional disabilitas using Groningen Activity Retriction Scale (GARS). Statistical test is using Rank Spearman. The result showed that the value of p=0,001, it means that there is a relationship between the status of the dimensia with functional disabilitas on the elderly and the value of r=-0,413, it means the higher of MMSE the lower of GARS score, so the reverse.